The effect of Different Levels of Probiotics and Demavate Vitamin Mixture on the product traits and rumen environment of Local Goat Kids - nasser, ali; Maithem K, Ali AL-Galiby, Maithem K, Ali AL-Galiby (University of Thi-Qar Journal of agricultural research, 2025)
This experiment was conducted at the animal field belonging to the College of Agriculture and Marshes/ University of Thi-Qar during the period from 15/9/2024 to 22/12/2025 to study the effect of different inclusion levels of a probiotic supplement and the vitamin mixture Demavate (AD3E) on the product traits of local goat kids, The experimental animals were assigned to five treatments, The results of the current study indicated a significant increase in body weight in T3 and T4 compared to the control group by the eighth week of the trial, reaching 25.13 and 26.30 kg, respectively. By the tenth week, T2, T4, and T5 showed superior final body weights, recording 29.16, 29.93, and 29.73 kg, respectively. In terms of total weight gain, T2 and T5 demonstrated the highest values at 11.90 and 11.29 kg, respectively, compared to the control. Daily weight gain was significantly higher in T3, T2, and T5, which recorded 141.66, 134.52, and 130.55 grams per day, respectively. No significant differences were observed in total feed intake among the treatment groups. However, the feed conversion ratio was significantly better in the control group (T1), which recorded a value of 10.03 kg feed per kg of weight gain, outperforming T2, T3, and T5.The treatment group T2 showed superior ruminal pH values on day 45 of the experiment before feeding compared to treatments T3 and T4, recording a value of 5.76. Additionally, T2 outperformed all other treatments three hours after feeding, with a pH of 5.95. On day 84 before feeding, treatment T4 recorded the highest ruminal pH (6.68), whereas three hours post-feeding, treatment T5 showed the highest pH value (5.86).A significant increase in the number of cellulolytic bacteria was observed in treatment T5 on day 45 before feeding, recording a value of 21.74 CUF ×10⁸, compared to other treatments. Three hours post-feeding, treatments T4 and T5 outperformed the others with values of 7.75 and 7.64 CUF ×10⁸, respectively. On day 84 before feeding, T5 again showed superiority with a value of 3.38 CUF ×10⁸, and after three hours, both T4 and T5 recorded the highest values: 8.53 and 8.42 CUF ×10⁸, respectively.